Postsynthetic in situ polymerization of a diamine-appended MOF for humidity-tolerant CO2 capture - Choe, Jong Hyeak; Kim, Hyojin; Shin, Dong Yun; Kim, Namju; Cheon, Gayoung; Yun, Hongryeol; Youn, Jeongwon; Lee, Jung-Hoon; Hong, Chang Seop (Elsevier BV, 2025)
Although diamine-appended Mg2(dobpdc) (dobpdc4− = 4,4′-dioxidobiphenyl-3,3′-dicarboxylate) exhibits excellent CO2 capture performance, its reusability under humid conditions is severely limited due to the loss of diamine groups caused by water vapor. This degradation becomes more pronounced at higher humidity levels. To address this issue, we coated Mg2(dobpdc) with poly(divinylbenzene) (PDVB) via postsynthetic in-situ polymerization, producing MOF/PDVB–X (X = 1, 3, 5) composites. Transmission electron microscopy confirmed that MOF/PDVB–3 and MOF/PDVB–5 possessed a hydrophobic PDVB layer on the MOF surface. Subsequent functionalization with N-ethylethylenediamine (een) afforded een–MOF/PDVB composites. Notably, een–MOF/PDVB–5 displayed outstanding stability, maintaining high CO2 adsorption capacity during prolonged ambient air exposure, as well as in repeated humid CO2 adsorption–desorption and humid breakthrough cycles, even at a significantly high relative humidity of 90 %. These findings demonstrate that PDVB coating offers a simple yet effective strategy to produce water-resistant, amine-functionalized adsorbents with excellent CO2 capture performance and long-term durability for practical applications.